Improving Locomotor Skills Through the Bentengan Traditional Game Based on Living Values Education - Rika Fauziyah Saprudin; Rahmad Khodari; Auliya Aenul Hayati (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study aims to test the effectiveness of the Bentengan traditional game, based on Living Values Education (LVE), in improving the locomotor skills of Year 4 pupils at SDN Kanggraksan. A mixed-methods approach with an explanatory sequential design was employed. The quantitative component used a quasi-experimental One Group Pre-test-Post-test design involving 28 pupils. Locomotor skills were measured using the TGMD-2 locomotor subtest, whilst LVE value inter-nalisation was observed using a structured observation sheet. The intervention consisted of 4 sessions (2×35 minutes). Quantitative analysis included the Wil-coxon Signed-Rank Test and N-Gain; qualitative analysis utilised the Miles & Hu-berman model. Results showed an increase in average locomotor skills from 22.29 to 37.79 (69.57% gain), with a highly significant difference (Z = -4.631; p < 0.001). The average N-Gain was 0.60 (moderate to high) and all students im-proved. Qualitative data revealed that LVE value internalisation (cooperation, responsibility, respect) occurred progressively, with observation scores develop-ing from 22/60 (Insufficient) to 59/60 (Very Good). The Bentengan traditional game based on LVE is effective in improving locomotor skills whilst internalising character values, recommended as a holistic approach for Physical Education teachers.